1994
DOI: 10.1002/ddr.430330406
|View full text |Cite
|
Sign up to set email alerts
|

New 1,4‐benzothiazepine derivative, K201, demonstrates cardioprotective effects against sudden cardiac cell death and intracellular calcium blocking action

Abstract: In order to find drugs with suppressive effects against sudden cardiac cell dea ... UOl of the response to K t was less marked than that by diltiazem. Its inhibition of the response to NE was greater than that by diltiazem or KT362. K201 demonstrated an inhibitory effect on binding of cardiac annexin V with actin dependent on calcium concentration, but diltiazem and KT362 did not demonstrate any action to inhibit this reaction. These results indicate that K201 was a more effective cardioprotectant than propran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
85
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…These IC 50 values were a few to 10 times smaller than those to inhibit I Na , I Ca and I K1 in guineapig ventricular cells (Kimura et al, 1999). In addition, the concentrations to inhibit I K and I K.ACh were comparable to or smaller than those to elicit cardioprotective e ects (Inagaki et al, 2000;Kaneko, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These IC 50 values were a few to 10 times smaller than those to inhibit I Na , I Ca and I K1 in guineapig ventricular cells (Kimura et al, 1999). In addition, the concentrations to inhibit I K and I K.ACh were comparable to or smaller than those to elicit cardioprotective e ects (Inagaki et al, 2000;Kaneko, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…JTV-519 is a benzothiazepine derivative possessing protective e ects against myocardial injuries induced by Ca 2+ overload and ischaemia/reperfusion (Kaneko, 1994;Inagaki et al, 2000). The underlying mechanism(s) of the cardioprotective e ect have not been well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 JTV519(K-201) is a 1,4-benzothiazepine derivative 25 that has been shown to protect against Ca 2+ overload. 26 Two recent reports have suggested that a major effect of this annexin blocker is to improve defective ryanodine receptor gating by enhancing the coupling between FKBP and RYR2 proteins to stabilize the release channel. 11 , 27 Other reports have shown that it can affect several sarcolemmal ion channels, e.g., L-type Ca 2+ channel.…”
Section: Discussionmentioning
confidence: 99%